Ways gifted children can study the future - Torrance, E. Paul
Described here are only a few methods that are emerging for helping children study the future. These methods are especially appealing to gifted students because they are challenging and stretch thier minds, imaginations, and aspirations. Such stretching now by gifted students may prevent shock and inadequate solutions in the future.
Keywords: Gifted children -- Education